Three Types of Ethno-Specificity in Phraseology: Ethno-Linguistic, Ethno-Cultural, and Ethno-Cognitive Specificity - Gutovskaya, Marina (Respectus Philologicus, 2015)
The ethno-specific phraseology – the phraseology which manifests interlanguage differences – is contemplated in the paper considering the phraseology corpora of the Russian and English languages. The popular opinion that ethno-specificity in phraseology is predetermined solely by unique features of the national culture is questioned. The three types of phraseological ethno-specificity are differentiated: ethno-linguistic (ensured by distinctive features of the national language), ethno-cultural (connected with the originality of the national culture), and ethno-cognitive (ordained by the uniqueness of the national worldview). The characteristics of the phraseological units that belong to each of the three types of ethno-specificity are enumerated, and the circles of questions on the ethno-specific phraseology to be studied within traditional linguistics, cultural linguistics, and cognitive linguistics are outlined. The possibility of coexistence of several types of ethno-specificity in one phraseological unit is shown. It is noted that in order to comprehend ethno-specific phraseological units of the three types a different degree of immersion in the foreign linguistic-cultural-cognitive space is required.
Keywords: Phraseology; Ethno-Specificity; Ethno-Linguistic; Ethno-Cultural; Ethno-Cognitive Specificity